Prevalence of impacted third molars and the reason for extraction in Saudi Arabia - Lina Alfadil; Emtenan Almajed (Elsevier, 2020)
Purpose: This study aims to record the current pattern of third molar impactions and relevant reasons for extraction in Riyadh, Saudi Arabia. We hypothesized that the principal reason for extraction was elective. Material and Methods: Orthopantomograms (OPG) radiographs and electronic files relating to 4000 patients were retrospectively collected from patients between the ages of 21 and 50 years old. Of these, 1014 were included in this study (514 females, 500 males). The classification was determined according to the Winter, Pell, and Gregory classification. The analysis was done using the chi-square (χ2) test, with SPSS version 25 (IBM, Inc, Chicago, IL). A p-value of < 0.05 was considered statistically significant. Results: A total of 2240 impacted third molars were found with no gender predilection. Impaction was more commonly found in the mandible (58.5%) than the maxilla (41.5%). The most common reason for extraction was 'asymptomatic; prophylactic indication' (66.8%), followed by 'symptomatic' (33.2%). Vertical angulation was most common in the maxilla (56.5%), and mesioangular impaction in the mandible (40.5%). Conclusion: There is a high rate of third molar impaction in the central region of Saudi Arabia. It is more likely to occur in the mandible than the maxilla with no gender predilection. The majority of the patients were referred for elective asymptomatic reasons. Mesio-angular impaction is mostly found in the mandible and vertical angulation in the maxilla. Both arches had a C level depth and Class I Ramus relationship. Further studies should be conducted with the wider Kingdom of Saudi Arabia so that the population can be more accurately represented.